2015
DOI: 10.1371/journal.pone.0120949
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of the Calcified Zone of Articular Cartilage in Post-Traumatic Osteoarthritis in Rat Knees

Abstract: ObjectivesThis study aimed to investigate the pathology occurring at the calcified zone of articular cartilage (CZC) in the joints afflicted with post-traumatic osteoarthritis (PTOA).MethodsRats underwent bilateral anterior cruciate ligament (ACL) transection and medial meniscectomy to induce PTOA. Sham surgery was performed on another five rats to serve as controls. The rats were euthanized after four weeks of surgery and tibial plateaus were dissected for histology. The pathology of PTOA, CZC area and the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…First, the high frequency roughness disappears (entrapment of the chondrocytes), then the low frequency undulations start to appear (uneven increase in calcification) and in the end (after the cartilage is eroded), the tidemark is completely smoothed by physical force of the bones grinding together. When comparing our results with the literature, similar results with TMR have been reported in histomorphometric analyses of rat CC in a post-traumatic OA model 31 . This previous study found that the TMR decreased in tibial plateaus of rats with increasing OA progression (Mankin et al 45 score).…”
Section: Tmnumber Number Of Tidemarks From Histological Sectionssupporting
confidence: 89%
See 1 more Smart Citation
“…First, the high frequency roughness disappears (entrapment of the chondrocytes), then the low frequency undulations start to appear (uneven increase in calcification) and in the end (after the cartilage is eroded), the tidemark is completely smoothed by physical force of the bones grinding together. When comparing our results with the literature, similar results with TMR have been reported in histomorphometric analyses of rat CC in a post-traumatic OA model 31 . This previous study found that the TMR decreased in tibial plateaus of rats with increasing OA progression (Mankin et al 45 score).…”
Section: Tmnumber Number Of Tidemarks From Histological Sectionssupporting
confidence: 89%
“…To date, most studies investigating the tidemark or channels through the calcified layer are done from 5 mm thick histological sections 13,30,31 . For instance, studies have been conducted to assess how the tidemark roughness (TMR) is altered as a function of OA 30,31 . Roughness of a 2D surface can be easily calculated as a ratio between the true length of the surface and the projected length of that surface, where the minimum value of one defines a perfectly smooth surface 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Sample scores were evaluated by two independent observers. Moreover, we performed an analysis of histological characteristics, including cartilage thickness, roughness, and relative staining intensity, using Safranin O and fast green 25 . For details see Supplementary material and methods.…”
Section: Histological Analysismentioning
confidence: 99%
“…Meniscal injuries are highly prevalent and often treated by arthroscopic meniscal debridement or Mx . Mx increases the relative risk for PTOA in humans sixfold and in animal models has been validated to lead to PTOA . The Mx model is used to study biomechanical destabilization and biological changes to the contact surfaces.…”
Section: Surgically Induced Animal Models Of Post‐traumatic Osteoarthmentioning
confidence: 99%